(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2025)
The history textbooks authored by Luis G. Benítez are remembered today as the mandatory textbooks of the Stronist educational system, a conviction reinforced by a series of investigations that purged all culpability within paraguayan historiography during the Stronist era from a single historian, exonerating the rest. However, a detailed analysis of other textbooks, especially that of Julio César Chaves, demonstrates that this image, established since the end of the paraguayan dictatorship, is erroneous, and that studies without a solid empirical basis only reinforced it. This article compares the textbooks by Benítez and those by Chaves in order to refute the myth of the “single textbook” and the idea that the majority of paraguayan historiography did not collaborate with the Stronist regime, but quite the opposite, since different texts and authors circulated that shared the same historiographical matrix proposed by Benítez.